Caso de estudio: planeamiento estratégico integral de Traditional Trade Audit SAC - Inga Yáñez, Mauricio (2023)
The objective of this professional sufficiency work is to analyze the strategic plan of Traditional Trade Audit, a company specializing in trade marketing point-of-sale auditing and execution. The development is divided into five chapters that allow for an evaluation of the current situation of the company and the proposal of strategies aligned with its objectives. The first chapter, the introduction, establishes the context and importance of a strategic plan in today's business environment. It emphasizes the need for Traditional Trade Audit to adapt its strategy to a constantly changing and competitive market. The second chapter, strategic planning, delves into the internal and external analysis of Traditional Trade Audit. It assesses its resources, capabilities, and competencies, as well as market trends, regulations, and emerging opportunities. This analysis provides a solid foundation for strategy formulation. The third and fourth chapter focuses on strategy formulation. Specific strategies for Traditional Trade Audit are proposed based on the previous analysis. These strategies may include geographic expansion, service diversification, or operational efficiency improvement. The last chapter, implementation and control, addresses how Traditional Trade Audit will carry out the proposed strategies and how results will be measured. Key performance indicators are established under the design of a strategic control map to ensure effective implementation.